STEAM Education Oriented Fostering Pre-Primary Teachers’ Capacity in Organizing Sculpture Activities - Não Thị Diễm Tuy; Bùi Văn Hồng (Journal of Technical Education Science, 2024)
The objective of this study is to develop and implement a training program to enhance preschool teachers’ capacity to organize arts activities based on the STEAM (Science, Technology, Engineering, Arts, and Mathematics) education approach. The research is carried out through the following steps: (1) Surveying the current status of preschool teachers’ capacity to organize arts activities and their understanding of STEAM education; (2) Designing the training program based on the survey results and reviewing effective training models; (3) Organizing training activities for teachers and evaluating the outcomes. The study employs both quantitative and qualitative methods to collect and analyze data. The research findings will provide evidence of the effectiveness of the training program, thereby proposing solutions to improve preschool teachers’ capacity to organize arts activities aligned with the STEAM education approach. This study can contribute to enhancing the quality of early childhood education and meeting the professional development needs of teachers in the context of educational innovation.